Saying I Know You – Conversational Analysis On Internet-Chatting By Dating Couples – - Hiroaki Chijiiwa (Bina Nusantara University, 2012)
In casual conversations, Japanese people do not refer to their intimacies saying “We are close this much.” It is difficult to create special scales for intimacies because the term of “Intimacy” is too abstract and vague. However, don’t Japanese people really scale their intimacies during their conversations? In this study, the researcher aimed to describe strategies of intimacies in Japanese using method of Conversational Analysis onto dating couple’s casual internet chat data and analyzed “how people show their intimacies to opponent through the conversations.” For conclusion we can say; Japanese people tend to say “I know you” in indirect way to emphasize the opponent’s “the illusion of transparency”.